School Information System (SIS) - Hadzli Zul , Hamran (UTeM, 2009)
School Information System (SIS) is a web based application that developed to help school management manage their student's information, teacher's information, teaching and time table management. This application also allows the parent to access on-line their children information assessment and achievement. SIS used Rapid Application Development (RAD) as development methodology. Active Server Page (ASP) is a programming language that used to develop this application. The target users of this application are school staff such as teachers, administrator, students and parent. ?'he main objective of the development this application is to solve problem that occurs from present system and manual method that being used. In addition, SIS is developing with security features such as using of password and user level access to the system. School management also can manage their students, teachers, subjects and e~arnil~&ioinnf ormation efficiently and effectively. The main added feature to this system is time table management. Online accesses allow user to access the application at anytime and anywhere as long as they are connected to the internet. Centralize and systematic data storage can reduce duplication of information and increase reusability of information.